Contribuição ao estudo fitoquímico de dalbergia ecastophyllum (l.) Taub. (fabaceae) - Maciel, Rafaela Dos Santos Soares (2016)
Dalbergia ecastophyllum (L.) Taub., popularly known as “rabo-de-bugio” or “marmelo-do-mangue”, is a species of the Fabaceae family, with expressive commercial value, since propolis comes from resinous exudates present in the stem of this species. This study aimed to contribute the phytochemistry study of Dalbergia (Fabaceae) genus through the phytochemical study of D. ecastophyllum species. The plant material (leaves and roots) was collected in Rio Tinto - Paraiba and deposited in the Herbarium of the Department of Systematics and Ecology – UFPB with the 45738 code (JPB). For phytochemical study, the plant material after drying and pulverization, was subjected to extraction processes, partition and chromatography to isolate the chemical constituents. The chemical structures thereof were determined by spectroscopic methods and comparisons with literature data. The fractions of the leaves allowed isolation of 13²-17³-hydroxy-ethoxypheophorbide A, pheophytin A, phytol and isoquercitrin substances. Since fractions of the roots were isolated the cedrol, acetate morolic acid, daidzein, formononetin, β-sitosterol and stigmasterol; and 4-geranyl-3,5-dihydroxy-4'-methoxy-trans-stilbene. The latter substance was isolated for the first time in the literature. The ethyl acetate fraction of the leaves has excellent antioxidant activity against DPPH (IC50 = 0.85 ± 0.236 g/ml).